(3GdSdhc hGdehGYX Edi cd ZadGf hjGbXs - (3GdMHTj GddJjfj GdTGaYj GdbGOQj, Wg Hf EHQGgje Hf Wg Hf jSjf Hf eMeOs ((3Ydj Hf QLHs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Sdec Hef GUWaGg GdUQGW GdeSJbje bO SCdfj HYV ef dG jSYfj EdG ELGHJg Cf CfXe cJGHG LGeYG ef eJaQbGJ cdGe GdCFeI GdeYJHQjf s
(3BNQgG (B:s
(3hQhi ef MOjK GHf eSYhO QVj Gddg Yfg ef Ccd dbeI de JbHd dg UdGI CQHYjf jheG , hef MOjK GHf YeQ QVj Gddg JYGdi YfgeG ef de jHGd ef Cjf GcJSH GdeGd GdMQGe de jHGd Gddgef Cjf CONdg GdfGQ, Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eUWai Hf YHO GdhgGH GdUdGMj GdUGdMj , SfI (B: 1222 (3g`s
Keywords: (3GdJUha hGdBOGH GdTQYjIs